2011
DOI: 10.1007/s00167-011-1570-5
|View full text |Cite
|
Sign up to set email alerts
|

Autologous platelet-rich plasma gel to reduce donor-site morbidity after patellar tendon graft harvesting for anterior cruciate ligament reconstruction: a randomized, controlled clinical study

Abstract: Prospective randomized controlled study, Level I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
127
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(133 citation statements)
references
References 25 publications
3
127
1
2
Order By: Relevance
“…However, in an intraoperative setting, PRP may be injected as a liquid or gel 52 , or delivered as a fibrin matrix (platelet-rich fibrin matrix, PRFM) 53 . Most of the surgical applications of PRP for hip and pelvic pathology are novel, with few studies currently in the literature.…”
Section: Surgical Applicationsmentioning
confidence: 99%
“…However, in an intraoperative setting, PRP may be injected as a liquid or gel 52 , or delivered as a fibrin matrix (platelet-rich fibrin matrix, PRFM) 53 . Most of the surgical applications of PRP for hip and pelvic pathology are novel, with few studies currently in the literature.…”
Section: Surgical Applicationsmentioning
confidence: 99%
“…Gels, such as collagen type I [3,4] and platelet-rich plasma [5], have been investigated but their use is currently limited due to issues with purity and regulatory standards (such as the FDA and MHRA), and their inherent weak mechanical properties that are essential for this type of tissue. Electrospun fibre scaffolds are finding increasing use…”
Section: Introductionmentioning
confidence: 99%
“…17,24 The use of PRP in the patellar tendon harvest site reduced donor site morbidity after ACL reconstruction. 9 However, other high-level evidence studies have not shown benefits in the use of PRP. A level I study found PRP to be as efficient as saline in Achilles tendinopathy treatment.…”
mentioning
confidence: 99%